"2x_1+x_2+2x_3=0,"
"x_1+6x_3=0,"
"x_2+x_3=0."
"(R_1 \\gets R_1-2R_2)"
"x_2+2x_3-12x_3=0,"
"x_1+6x_3=0,"
"x_2+x_3=0."
"(R_1 \\gets R_1-R_3)"
"-11x_3=0,"
"x_1+6x_3=0,"
"x_2+x_3=0."
Thus, "x_1=0, x_2=0, x_3=0."
A basis for the solution space is "(0,0,0)," the dimension of this space in "R^3" is 0.
2."2x=3y-5z"
"x=3y\/2-5z\/2"
"\\begin{pmatrix}\n ( 3\/2) y-(5\/2)z \\\\\n y\\\\\nz\n\\end{pmatrix}=\\begin{pmatrix}\n (3\/2) \\\\\n 1 \\\\\n 0\n\\end{pmatrix}y+\\begin{pmatrix}\n - 5\/2 \\\\\n 0\\\\\n 1\n\\end{pmatrix}z"
{"v_1,v_2" }={(3/2,1,0),(5/2,0,1)} spans R3
We just have to prove that "a_1,a_2=0" in "a_1v_1+a_2v_2=0"
"a_1(3\/2,1,0)+a_2(-5\/2,0,1)=0"
"(3\/2)a_1-(5\/2)a_2=0"
"a_1=0"
"a_2=0"
So, { "v_1,v_2" } is the basis of the subspace in R3, the dimension of the subspace in "R^3" is 2.
3.(D)
"v_1=(1,-1,3,-6)"
"v_2=(-3,4,-12,24)"
"v_3=(x_1,y_1,z_1,w_1)"
"v_4=(x_2,y_2,z_2,w_2)"
"a_1v_1+a_2v_2+a_3v_3+a_4v_4=0"
"a_1 (1,-1,3,-6) +a_2(-3,4,-12,24)+a_3(x_1,y_1,z_1,w_1)+a_4 (x_2,y_2,z_2,w_2) =0"
From above we obtain the following equation:
"a_1-3a_2+x_1a_3+x_2a_4=0"
"-a_1+4a_2+y_1a_3+y_2a_4=0"
"3a_1-12a_2+z_1a_3+z_2a_4=0"
"-6a_1+24a_2+w_1a_3+w_2a_4=0"
From the options we put the values of v3 and v4 in the above equations.
"a_1=a_2=a_3=a_4=0" only for D option.
Comments
Leave a comment